Nitrile cup seal robustness in the India Mark II/III hand pump system. (2021) - Ottosson, Hans J.; Mattson, Christopher A.; Johnson, Oliver K.; Naylor, Thomas A.
Abstract: Accessing clean water is a persistent and life-threatening challenge for millions of people in the world. Each hour, 400 children under the age of five die because of the lack of clean water. To help people get access to clean ground water, mechanical hand pumps are often used. Among the most ubiquitous is the India Mark II/III hand pump system, of which there are more than 4 million installed across the world. These are estimated to serve between 600 million and 1 billion people. But as with most mechanical systems, they degrade over time–leading to pumps becoming dysfunctional due to lack of required service. The pump's nitrile cup seals are the most common cause of dysfunctionality. The purpose of this paper is to analyze the robustness of the cup seals in the India Mark II/III hand pump system. In this paper, 110 off-the-shelf nitrile cup seals purchased by the authors in Uganda were tested and characterized. Leak and pump performance tests were performed in both static and dynamic settings and the correlations between performance and geometry and material properties of the cup seals were determined. This important baseline evaluation for the seals supports our future work to improve the longevity and robustness of the India Mark II/III hand pump system, with a focus on the cup seals. We believe that by finding the baseline of a product, engineers and designers will be able to improve its performance.